The relationship of the time of the emergence of distinguishing threshold anaerobic treatment of some of the variables of the electrical signal quartet to basketball players young people in terms of the Sports Technology - Mutshr, Firas (Journal of Physical Education, 2016)
The aim of the study to identify the time of the emergence of distinguishing threshold summit anaerobic treatment of electrical signals, learn about the time of the emergence of distinguishing threshold size anaerobic treatment of electrical signals in the quartet muscle to young players basketball technology in mineable sport, and two researchers assumptions to solve the problem of search according to these goals, and use the two researchers descriptive approach in a relational database relations on a sample of young players at the national center for the care of Sports Talent basketball’s (9) representing a proportion (30%) from their originally selected an intentional offense and variables tests of the study and implementation of the study of the Chairperson on the basis of technology laboratories sport was holding two tests and I am linking the two systems, according to the conditions and procedures on the body of each player is based performance on the bike inalienable, during the instrument cluster monitored system screen Device (Fit mate pro) imaging began the camera for your (EMG) synchronization is working at the threshold of the Codex Aliment Arius anaerobic treatment be imaging Camera directing toward the screen was pro synchronization is the minute points intermittent line which represents the time of the emergence of distinguishing threshold anaerobic treatment and the (EMG) register read the summit and space quartet on the issue, the sensors in a computer mobile PC to control the muscle fatigue quartet cleanness, two researchers concluded after dealing with the system of statistical pouch Social Statistical (SPSS) version (V24), the lack of time of the emergence of distinguishing threshold anaerobic treatment over the top of the electrical activity straight to the young players basketball is linked to the adversely with him, and increase the time the emergence of distinguishing threshold anaerobic treatment increases the size of the electrical activity straight The young players basketball it is linked to the pyknic line.